Performance study of centrifugal air compressor for proton exchange membrane fuel cell systems. Issue 1 (25th November 2021) - Liu, Yunxia; Zhao, Yuanyang; Yang, Qichao; Liu, Guangbin; Li, Liansheng; Gao, Zhicheng
Abstract: Air supply systems are essential subsystems in proton exchange membrane (PEM) fuel cell systems. Compressors are the key devices of air supply systems that greatly influence the characteristics of fuel cells. The simulation and experimental researches on a small centrifugal compressor with high rotation speed have been presented in this paper. Firstly, the input parameters of a compressor are obtained based on the output power and operating pressure of PEM fuel cells. Then, a prototype of small centrifugal compressors applied in PEM fuel cells is designed, simulated with the computational fluid dynamics (CFD) method, and tested in actual working conditions. Finally, the simulation results show that the internal flow in compressors affects the performance strongly. The discharge pressure of the simulation is close to the test data in the studied working conditions, and the maximum error is less than 6%. Abstract : Compressors are the key devices of air supply systems that greatly influence the characteristics of fuel cells. The simulation and experimental research on a small centrifugal compressor with high rotation speed is presented.